Nghiên cứu thành phần hóa học cây Chay (Artocarpus lakoocha Roxb.). I. Các hợp chất triterpen khung lupan - Bảo, Nguyễn Chí; Anh, Nguyễn Thị Hoàng; Sung, Trần Văn (Vietnam Journal of Chemistry, 2012)
Four triterpenes were isolated from the n-hexane and ethyl acetate extracts of Artocarpus lakoocha collected in Son La province. Their structures were elucidated by analysis of MS, NMR spectra and comparison with the published data. They are lup-20(29)-ene-3b-ol, lup-20(29)-ene-3b-acetate, lup-20(29)-ene-3-one and betulinic acid.